Castes in the old world and in the new - Horn, Margaretha Elise (My University, 1893)
Introduction: Theoretically, or in its primary sense, the term caste was applied to certain fixed divisions of society. By fixed divisions, I mean such divisions of society that if a man of ours comes within a certain class, neither he nor his posterity is able to pass into another. In short, the son must follow in the footsteps of his father. If the father is a priest, the son will be a priest, if a merchant, he will be a merchant, if the father is a servant, so will be the son.
Citation: Horn, Margaretha Elise. Castes in the old world and in the new. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Caste; Society; Father; Son; Theses; Manuscripts (documents)